Markedness: Contrasting Porter's Model with the Linguists Cited as Support - RUNGE, STEVEN E. (2016)
The linguistic concept of markedness underpins significant portions of Stanley Porter's "planes of discourse" model. The work of several linguists is regularly cited in conjunction with the development of his ideas with little other argumentation or explanation offered, creating the impression that his claims are consistent with and supported by the cited works. This article compares Porter's claims with those found in the primary literature cited and demonstrates that his markedness claims find little support there; however, Porter offers no rationale or linguistic justification for for such a dramatic departure from established linguistic methodology